2010
DOI: 10.1182/blood-2010-01-264754
|View full text |Cite
|
Sign up to set email alerts
|

S100A10 regulates plasminogen-dependent macrophage invasion

Abstract: The plasminogen activation system plays an integral role in the migration of macrophages in response to an inflammatory stimulus, and the binding of plasminogen to its cell-surface receptor initiates this process. Although previous studies from our laboratory have shown the importance of the plasminogen receptor S100A10 in cancer cell plasmin production, the potential role of this protein in macrophage migration has not been investigated. Using thioglycollate to induce a peritoneal inflammatory response, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(163 citation statements)
references
References 45 publications
7
154
2
Order By: Relevance
“…Also, in the absence of MMP9, macrophages were completely unable to respond to Plg for increased 3D invasion and matrix degradation, indicating its importance in the downstream proteolytic events initiated by uPA/Plg. Consistent with our data, Thio-Mw in the presence of Plg generate active MMP9 (63), and if these macrophages are elicited from MMP9 2/2 mice, they fail to respond to Plg for increased 3D invasion (64). In that study, MMP9 2/2 ThioMw had no defect in 3D invasion, which differs from our finding with MMP9 2/2 BMM and with uPA 2/2 Thio-Mw.…”
Section: Discussioncontrasting
confidence: 56%
“…Also, in the absence of MMP9, macrophages were completely unable to respond to Plg for increased 3D invasion and matrix degradation, indicating its importance in the downstream proteolytic events initiated by uPA/Plg. Consistent with our data, Thio-Mw in the presence of Plg generate active MMP9 (63), and if these macrophages are elicited from MMP9 2/2 mice, they fail to respond to Plg for increased 3D invasion (64). In that study, MMP9 2/2 ThioMw had no defect in 3D invasion, which differs from our finding with MMP9 2/2 BMM and with uPA 2/2 Thio-Mw.…”
Section: Discussioncontrasting
confidence: 56%
“…This suggestion is currently under investigation in our laboratory. Several Plg receptors have been shown to participate in Plainduced migration in vivo and in vitro (12)(13)(14)(15)45). These receptors have two common properties: they possess a carboxyl-terminal lysine residue that can bind Plg and they are not transmembrane proteins but become expressed on the cell surface by yet undefined pathways (46).…”
Section: Discussionmentioning
confidence: 99%
“…41 Analysis of cell surface ANXA2 has identified intact ANXA2 but failed to observe any truncated ANXA2. 37,39,40 Recently, we examined the molecular weight forms of ANXA2 at the endothelial cell surface by Western blotting. 41 Although native ANXA2 was easily detected, we were unable to detect any lower molecular weight (truncated) forms of ANXA2.…”
Section: The Role Of Anxa2 In Fibrinolysismentioning
confidence: 99%
“…34 Shortly after these reports, another group demonstrated the presence of S100A10 on the surface of endothelial cells and the reversible interaction of the C-terminal lysine of S100A10 with both tPA and plasminogen. 35,36 This group established that S100A10 was present in a heterotetrameric complex with ANXA2 on the surface of many cells 35,[37][38][39][40][41] and demonstrated that purified AIIt bound tPA and plasminogen via the C-terminal lysine of the S100A10 subunit without the participation of the ANXA2 subunit. 36,42,43 With the development of methods to deplete cells of ANXA2 and the report of defective fibrinolysis in the ANXA2 knockout mouse, 44 it appeared that ANXA2 might play a role in cellular fibrinolysis.…”
Section: Historical Perspectivementioning
confidence: 99%